Integrating Cultural Values in Counseling: The Role of Peumulia Jamee in Indigenous Counseling Practices for Acehnese - Nelissa, Zahra; Taufik, Agus; Nurihsan, Juntika; Adiwinata, Anne Hafina; Ahmad, Mazita (Universitas Negeri Padang, 2024)
Peumulia Jamee is one of the local wisdoms of the Acehnese people, which means respect and acceptance of guests. This tradition has strong cultural roots and religious values, making it an important social practice in forming relationships between individuals in Acehnese society. The goal of this study is to investigate how the Acehnese people perceive the Peumulia Jamee culture and how they implement its values in their daily lives. This study used a phenomenological approach to explore the experiences and views of the community regarding the Peumulia Jamee practice. We collected data through in-depth, semi-structured interviews conducted face-to-face with five informants who possess a deep understanding of Acehnese customs and traditions. Interviews were conducted with a semi-structured guide, allowing informants to express their views freely and in detail regarding the values of Peumulia Jamee. The data analysis revealed three main clusters, along with several emerging ones: (1) the basis and values of Peumulia Jamee culture, which encompasses beliefs from Islamic teachings, customs, and history as the foundation of culture; (2) practices and forms of honoring guests, which includes the themes of forms of honoring guests, honoring guests, and guest classification; and (3) ethics and social behavior, which includes the themes of ethics, verbal behavior, body part behavior, and manners. The results of this study are expected to provide deeper insight into the Peumulia Jamee tradition in forming a counseling approach based on local wisdom in Aceh, Indonesia.